Integrating 3D culture systems and gene editing technologies for precision medicine in hematological malignancies - Dhanasekar, Sariga; Meenakumari, B.; Kathirvel, Bargavi; Chandramouleeswari, K. (International Journal of Research in Medical Sciences, 2026)
Haematological malignancies comprise a diverse group of life-threatening systemic diseases in the blood, bone marrow, and lymphoid tissues, and their progression is strongly influenced by a supportive tumour microenvironment that drives proliferation and drug resistance. Drug development and personalised treatment using patient-derived cells are a tedious and expensive process, often conducted in 2D cell culture, which has many uncertainties and limitations due to poor mimicry of the microenvironment, cellular mechanisms, and morphological changes. Animal models also fail to fully replicate human pathobiology and are time-consuming. Alternatively, three-dimensional (3D) in vitro tissue modelling techniques can replicate the complex microenvironment, resembling the morphology, cell-cell interactions, and extracellular matrix (ECM) through methods like organoids, spheroids, tumoroids, and scaffold-based cultures. High-throughput drug screening in edited 3D cultures allows analysis of tumour interactions in haematological malignancies, for example, assessing gene-mediated drug resistance in AML within the marrow niche, depending on specific myeloma plasma cell cultures and their interactions with mesenchymal stem cells, along with susceptibility to CAR-T regulators and clinical translation in patient-derived therapies. The clinical translation of 3D culture and gene-editing–based in vitro models in leukemia, lymphoma, and multiple myeloma predicts cellular interactions with the tumour microenvironment, thereby enabling targeted treatment options for patients. This review highlights current progress in integrating gene editing with 3D culture system and emphasises their potential to enhance personalised drug discovery and preclinical testing in haematological malignancies.